MAKTABGACHA YOSHDAGI BOLALARNING IJTIMOIY MOTIVLARINI SHAKLLANTIRISH PEDAGOGIK MUAMMO SIFATIDA - Ismayilova, R.I. (SCIENCE and SOCIETY, 2024)
This article is devoted to the research of the formation of social motives of preschool children. It reveals the theoretical and practical foundations of the formation of social motives of preschool children. The formation of social motives of preschool children is described as a pedagogical problem.
Keywords: motive; social motive; motivation; socialization; pedagogical skill; didactic game; behavior